Social media-based advocacy in social work practice for domestic violence survivors: a mixed-methods study - Ratna Supiyah; Hannin Pradita Nur Soulthoni; Muhammad Arsyad; Dian Puspita Rizki; Sarpin (CV. Literasi Indonesia, 2026)
This study examines the role of social media in the digital advocacy practices of social workers at the Office of Women's Empowerment and Child Protection (DP3A) of Kendari City in handling domestic violence (DV) cases. Employing a sequential explanatory mixed-methods design, the study integrated content analysis and engagement metrics of the DP3A's official social media accounts on Instagram, Threads, and Facebook (Quantitative Phase) with semi-structured in-depth interviews with social workers, social media administrators, and DV survivors (Qualitative Phase). A total of 73 posts were analyzed. Findings reveal that institutional activity content dominates (42.5%), while service-oriented content, including reporting procedures, contact information, and confidentiality assurances, remains markedly limited. Advocacy and campaign content generated the highest average engagement (10.0 per post), indicating audience responsiveness to social messaging. Qualitative findings indicate that survivors prefer private communication channels due to fear and stigma, suggesting that low public engagement does not equate to content ineffectiveness. A digital advocacy process model encompassing four phases, digital information exposure, initial contact, preliminary assessment, and formal service referral, is proposed. The study recommends strengthening survivor-centered content strategies, developing digital response protocols, and fostering cross-sector collaboration to optimize social media as an advocacy instrument for domestic violence services.